PROMOSI KESEHAT AN MELALUI POS PEMBINAAN T ERPADU (POSBINDU) BERBASIS PASAR DI PASAR BANTUL - Titih Huriah (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
The double burden desease is one of the problems in the development of health. On the one hand there are still many infectious diseases that must be handled, but on the other hand, noncommunicable diseases are increases. The proportion of deaths due to no n- communicable diseases increased from 41.7% in 1995 to 49.9% in 2001, and increased to 59.5% in 2007. Increasing the prevalence of non-communicable diseases poses a serious threat especially in the elderly population. Community-based of non- communicable diseases control needs to be carried out, especially in locations where there is still minimal health care such in the market. Implementation procedures begin w ith permission, coordinate w ith market traders, prepare tools, health promotion media, and places used for program implementation. Activities in community service consists of anti-hypertensive exercises, measurement of weight and height, measurement of stomach circumference, checking blood pressure and blood sugar, health counseling, and supplementary feeding. Activity is carried out for three months. Evaluation of this activity is done by elderly health screening. The result of community service activities for 3 months showed significant decrease in elderly blood pressure, increased know ledge on cadres and improvement of market traders quality of life.